Relationship between heart rate variability and cognitive function in patients with enlarged perivascular space - Zhou, Dongyang; Lu, Chang; Su, Chunhe; Liu, Yuechen; Chen, Jing; Zhang, Feng; Bai, Hongying; Li, Qianqian (Frontiers in Aging Neuroscience, 2022)
Objective: To explore the relationship between heart rate variability (HRV), the brain distribution of enlarged perivascular space (EPVS), and cognitive impairment in patients with EPVS. Methods: The clinical and imaging data of 199 patients with EPVS were retrospectively analysed. EPVS load in the basal ganglia (BG) and centrum semiovale (CS) regions were assessed using the Potter's method. Cognitive function was evaluated using the Montreal Cognitive Assessment Scale. A logistic regression model was used to analyse the relationship between HRV and the brain distribution of EPVS and cognitive function of patients with EPVS. A receiver operating characteristic curve was used to assess the predictive value of HRV for cognitive function in patients with EPVS. Results: Of the 199 patients, 27 and 42 presented with severe BG-EPVS and cognitive impairment, respectively. Significant differences were observed in the root mean square of normal-normal (NN) intervals for the period of interest (rMMSD), the percentage of adjacent NN intervals greater than 50 ms (PNN50), and the ratio of low-frequency power (LF) to high-frequency power (HF) between the mild and severe BG-EPVS groups (P < 0.05). Patients who presented with and without cognitive impairment differed significantly in the standard deviation of NN intervals (SDNN), rMMSD, PNN50, total power, LF, and LF/HF (P < 0.05). rMMSD (odds ratio [OR] 0.871, 95% confidence interval [CI] 0.768–0.988) and LF/HF (OR 3.854, 95% CI 1.196–12.419) were independent influencing factors of BG-EPVS, and rMMSD (OR 0.936, 95% CI 0.898–0.976, P = 0.002) was an independent influencing factor of cognitive impairment in patients with EPVS. The optimal cut-off point was 0.312, with an area under the curve of 0.795 (95% CI 0.719–0.872, P < 0.01) for predicting cognitive impairment in patients with EPVS by rMMSD. Conclusions: Reduced HRV is involved in the pathophysiological mechanisms of the formation and development of BG-EPVS and is associated with cognitive impairment in patients with EPVS, independent of CS-EPVS. For patients with HRV changes but without autonomic nervous system symptoms, positive intervention may slow the occurrence or progression of EPVS and cognitive impairment in patients with EPVS.